Energy independence of the Collins asymmetry in p ↑ p collisions - STAR Collaboration (Physical Review Letters, 2025)
The STAR experiment reports new, high-precision measurements of the transverse single-spin asymmetries for π^{±} within jets, namely the Collins asymmetries, from transversely polarized p^{↑}p collisions at sqrt[s]=510 GeV. The energy-scaled distribution of jet transverse momentum, x_{T}=2p_{T,jet}/sqrt[s], shows a remarkable consistency for Collins asymmetries of π^{±} in jets between sqrt[s]=200 GeV and 510 GeV. This indicates that the Collins asymmetries are nearly energy independent, with, at most, a very weak scale dependence in p^{↑}p collisions. These results extend to high-momentum scales (Q^{2}≤3400 GeV^{2}) and enable unique tests of evolution and universality in the transverse-momentum-dependent formalism, thus providing important constraints for the Collins fragmentation functions.
Keywords: Asymmetry; Consistency (knowledge bases); Fragmentation (computing); High energy; Independence (probability theory); Polarization (electrochemistry); Transverse plane; Universality (dynamical systems); dept.phy

Measurement of In-Medium jet modification using direct Photon+Jet and π0+Jet correlations in p+p and central Au+Au collisions at sNN=200 GeV - STAR Collaboration (Physical Review Letters, 2025)
Keywords: Atomic physics; Hadron; Jet (fluid); Jet quenching; Materials science; Nuclear physics; Optics; Photon; Physics; Quark–gluon plasma; Quenching (fluorescence); Range (aeronautics); Thermodynamics; dept.phy

Measurement of directed flow in Au+Au collisions at √𝑠𝑁⁢𝑁=19.6 and 27 GeV with the STAR event plane detector - STAR Collaboration (Physical Review C, 2025)
In heavy-ion collision experiments, the global collectivity of final-state particles can be quantified by anisotropic flow coefficients (𝑣𝑛). The first-order flow coefficient, also referred to as the directed flow (𝑣1), describes the collective sideward motion of produced particles and nuclear fragments in heavy-ion collisions. It carries information on the very early stage of the collision, especially at large pseudorapidity (𝜂), where it is believed to be generated during the nuclear passage time. Directed flow therefore probes the onset of bulk collective dynamics during thermalization, providing valuable experimental guidance to models of the pre-equilibrium stage. In 2018, the Event Plane Detector (EPD) was installed in STAR and used for the Beam Energy Scan phase-II (BES-II) data taking. The combination of EPD (2.1<|𝜂|<5.1) and high-statistics BES-II data enables us to extend the 𝑣1 measurement to the forward and backward 𝜂 regions. In this paper, we present the measurement of 𝑣1 over a wide 𝜂 range in Au+Au collisions at √𝑠𝑁⁢𝑁= 19.6 and 27 GeV using the STAR EPD. The results of the analysis at √𝑠𝑁⁢𝑁= 19.6 GeV exhibit excellent consistency with the previous PHOBOS measurement, while elevating the precision of the overall measurement. The increased precision of the measurement also revealed finer structures in heavy-ion collisions, including a potential observation of the first-order event-plane decorrelation. Multiple physics models were compared to the experimental results. Only a transport model and a three-fluid hybrid model can reproduce a sizable 𝑣1 at large 𝜂 as was observed experimentally. The model comparison also indicates 𝑣1 at large 𝜂 might be sensitive to the QGP phase transition.
Keywords: Algorithm; Atomic physics; Charged particle; Computer science; Flow (mathematics); Ion; Mechanics; Nuclear physics; Physics; Pseudorapidity; Thermalisation; dept.phy; peer-reviewed

Energy dependence of polarized 𝛾⁢𝛾→𝑒+⁢𝑒− in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at RHIC - STAR Collaboration (Physical Review C, 2025)
We report the differential yields at mid-rapidity of the Breit-Wheeler process (𝛾⁢𝛾→𝑒+⁢𝑒−) in peripheral Au+Au collisions at √𝑠𝑁⁢𝑁=54.4 and 200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC), as a function of energy √𝑠𝑁⁢𝑁, 𝑒+⁢𝑒− transverse momentum 𝑝T, 𝑝2T, invariant mass 𝑀𝑒⁢𝑒, and azimuthal angle. In the invariant mass range of 0.4<𝑀𝑒⁢𝑒<2.6GeV/𝑐2 at low transverse momentum (𝑝T<0.15GeV/𝑐), the yields increase while the pair √⟨𝑝2T⟩ decreases with increasing √𝑠𝑁⁢𝑁, a feature that is correctly predicted by the QED calculation. The energy dependencies of the measured quantities are sensitive to the nuclear form factor, infrared divergence and photon polarization. The data are compiled and used to extract the charge radius of the Au nucleus.
Keywords: Computer science; dept.phy; peer-reviewed

Onset of Constituent Quark Number Scaling in Heavy-Ion Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
Partonic collectivity is one of the necessary signatures for the formation of quark-gluon plasma in high-energy nuclear collisions. Number of constituent quarks (NCQ) scaling has been observed for hadron elliptic flow v_{2} in top energy nuclear collisions at the Relativistic Heavy Ion Collider and the LHC, and this has been theoretically suggested as strong evidence for partonic collectivity. In this Letter, a systematic analysis of v_{2} of π^{±}, K^{±}, K_{S}^{0}, p, and Λ in Au+Au collisions at sqrt[s_{NN}]=3.2, 3.5, 3.9, and 4.5 GeV, with the STAR experiment at the Relativistic Heavy Ion Collider, is presented. NCQ scaling is markedly violated at 3.2 GeV, consistent with a hadronic-interaction dominated equation of state. However, as the collision energy increases, a gradual evolution to NCQ scaling is observed. This beam-energy dependence of v_{2} for all hadrons studied provides evidence for the onset of dominant partonic interactions by sqrt[s_{NN}]=4.5  GeV.
Keywords: Heavy ion; Ion; Nuclear physics; Particle physics; Physics; Quark; Scaling; Scaling law; dept.phy

Measurement of Two-Point Energy Correlators within Jets in p+p Collisions at sqrt[s]=200 GeV - STAR Collaboration (Physical review letters, 2025)
Hard-scattered partons ejected from high-energy proton-proton collisions undergo parton shower and hadronization, resulting in collimated collections of particles that are clustered into jets. A substructure observable that highlights the transition between the perturbative and nonperturbative regimes of jet evolution in terms of the angle between two particles is the two-point energy correlator (EEC). In this Letter, the first measurement of the EEC at RHIC is presented, using data taken from 200 GeV p+p collisions by the STAR experiment. The EEC is measured both for all the pairs of particles in jets and separately for pairs with like and opposite electric charges. These measurements demonstrate that the transition between perturbative and nonperturbative effects occurs within an angular region that is consistent with expectations of a universal hadronization regime that scales with jet momentum for a given initiator flavor. Additionally, a deviation from Monte Carlo predictions at small angles in the charge-selected sample could result from mechanics of hadronization not fully captured by current models.
Keywords: Collimated light; Hadronization; Jet (fluid); Momentum (technical analysis); Monte Carlo method; Observable; Parton; Parton shower; Substructure; dept.phy

Precision Measurement of Net-Proton-Number Fluctuations in Au+Au Collisions at RHIC - STAR Collaboration (Physical review letters, 2025)
We report precision measurements on cumulants (C_{n}) and factorial cumulants (κ_{n}) of (net) proton number distributions up to fourth order in Au+Au collisions over center-of-mass energies sqrt[s_{NN}]=7.7-27  GeV from phase II of the Beam Energy Scan program at RHIC. (Anti)protons are selected at midrapidity (|y|<0.5) within a transverse momentum range of 0.4<p_{T}<2.0  GeV/c. Relative to various noncritical-point model calculations and peripheral collision 70%-80% data, the net proton C_{4}/C_{2} measurement in 0%-5% collisions shows a minimum around 19.6 GeV for significance of deviation at ∼2-5σ. A minimum in C_{4}/C_{2} with respect to a noncritical baseline is expected to be a characteristic feature of the signature associated with a critical point in the QCD phase diagram. In addition, deviations from noncritical baselines around the same collision energy region are also seen in proton factorial cumulant ratios, especially in κ_{2}/κ_{1} and κ_{3}/κ_{1}. Dynamical model calculations including a critical point are called for in order to understand these precision measurements.
Keywords: Net (polyhedron); Nuclear physics; Physics; Proton; dept.phy

Precision measurement of the longitudinal double-spin asymmetry for dijet production at intermediate pseudorapidity ffiffi in polarized pp collisions at √s = 200 GeV - STAR Collaboration (Physical Review D, 2025)
The STAR Collaboration reports precise measurements of the longitudinal double-spin asymmetry, ALL, for dijet production with at least one jet at intermediate pseudorapidity 0.8 < ηjet < 1.8 in polarized proton-proton collisions at a center-of-mass energy of 200 GeV. This study explores partons scattered with a longitudinal momentum fraction (x) from 0.01 to 0.5, which are predominantly characterized by interactions between high-x valence quarks and low-x gluons. The results are in good agreement with previous measurements at 200 GeV with improved precision and are found to be consistent with the predictions of global analyses that find the gluon polarization to be positive. In contrast, the negative gluon polarization solution from the JAM Collaboration is found to be strongly disfavored. © 2025 American Physical Society
Keywords: Asymmetry; Computer science; Particle physics; Physics; Production (economics); Pseudorapidity; Spin (aerodynamics)

Measurements of ϒ states production in p + p collisions at √s = 500 GeV with STAR: Cross sections, ratios, and multiplicity dependence - STAR Collaboration (Physical Review D, 2025)
We report measurements of ϒ(1S), ϒ(2S) and ϒ(3S) production in p + p collisions at √s = 500 GeV ffiffi by the STAR experiment in year 2011, corresponding to an integrated luminosity Lint = 13 pb−1. The results provide precise cross sections, transverse momentum (pT) and rapidity (y) spectra, as well as cross section ratios for pT < 10 GeV=c and |y| < 1. The dependence of the ϒ yield on charged particle multiplicity has also been measured, offering new insights into the mechanisms of quarkonium production. The data are compared to various theoretical models: the color evaporation model (CEM) accurately describes the ϒ(1S) production, while the color glass condensate + nonrelativistic quantum chromodynamics (CGC + NRQCD) model overestimates the data, particularly at low pT. Conversely, the color singlet model (CSM) underestimates the rapidity dependence. These discrepancies highlight the need for further development in understanding the production dynamics of heavy quarkonia in high-energy hadronic collisions. The trend in the multiplicity dependence is consistent with CGC/saturation and string percolation models or ϒ production happening in multiple parton interactions modeled by PYTHIA8. © 2025 American Physical Society
Keywords: Algorithm; Mathematics; dept.phy

Temperature measurement of Quark-Gluon plasma at different stages - STAR Collaboration (Nature Communications, 2025)
In a Quark-Gluon Plasma (QGP), the fundamental building blocks of matter, quarks and gluons, are under extreme conditions of temperature and density. A QGP could exist in the early stages of the Universe, and in various objects and events in the cosmos. The thermodynamic and hydrodynamic properties of the QGP are described by Quantum Chromodynamics (QCD) and can be studied in heavy-ion collisions. Despite being a key thermodynamic parameter, the QGP temperature is still poorly known. Thermal lepton pairs (e+e− and μ+μ−) are ideal penetrating probes of the true temperature of the emitting source, since their invariant-mass spectra suffer neither from strong final-state interactions nor from blue-shift effects due to rapid expansion. Here we measure the QGP temperature using thermal e+e− production at the Relativistic Heavy Ion Collider (RHIC). The average temperature from the low-mass region (in-medium ρ0 vector-meson dominant) is (2.01 ± 0.23) × 1012 K, consistent with the chemical freeze-out temperature from statistical models and the phase transition temperature from Lattice QCD. The average temperature from the intermediate mass region (above the ρ0 mass, QGP dominant) is significantly higher at (3.25 ± 0.60) × 1012 K. This work provides essential experimental thermodynamic measurements to map out the QCD phase diagram and understand the properties of matter under extreme conditions. © The Author(s) 2025.
Keywords: Measure (data warehouse); Phase diagram; Plasma; Quantum chromodynamics; Quark–gluon plasma; Temperature measurement; Thermal; Transition temperature; Work (physics); dept.phy

Electric-charge-dependent directed flow splitting of produced quarks in Au+Au collisions - STAR Collaboration (Physics Letters B, 2025)
We report directed flow (v1) of multistrange baryons (Ξ and Ω) and improved v1 data for K−, p¯, Λ¯ and ϕ in Au+Au collisions at sNN=27 and 200 GeV from the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). We focus on particles whose constituent quarks are not transported from the incoming nuclei but instead are produced in the collisions. At intermediate impact parameters, we examine quark coalescence behavior for particle combinations with identical quark content, and search for any departure from this behavior (“splitting”) for combinations having non-identical quark content. Under the assumption of quark coalescence for produced quarks, the splitting strength appears to increase with the electric charge difference of the constituent quarks in the combinations, consistent with electromagnetic effect expectations.
Keywords: Directed flow; Electric charge; Electromagnetic field; Heavy-ion collisions; Strangeness; dept.phy; peer-reviewed

Light nuclei femtoscopy and baryon interactions in 3 GeV Au+Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2025)
We report the measurements of proton-deuteron (p-d) and deuteron-deuteron (d-d) correlation functions in Au+Au collisions at sNN = 3 GeV using fixed-target mode with the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). For the first time, the source size (RG), scattering length (f0), and effective range (d0) are extracted from the measured correlation functions with a simultaneous fit. The spin-averaged f0 for p-d and d-d interactions are determined to be -5.28 ± 0.11(stat.) ± 0.82(syst.) fm and -2.62 ± 0.02(stat.) ± 0.24(syst.) fm, respectively. The measured p-d interaction is consistent with theoretical calculations and low-energy scattering experiment results, demonstrating the feasibility of extracting interaction parameters using the femtoscopy technique. The reasonable agreement between the experimental data and the calculations from the transport model indicates that deuteron production in these collisions is primarily governed by nucleon coalescence.
Keywords: dept.phy; peer-reviewed

Hyperon global polarization in isobar Ru+Ru and Zr+Zr collisions at sNN=200GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The polarization of Λ , Λ ¯ , Ξ − , and Ξ ¯ + hyperons along the angular momentum of the system has been measured in isobar collisions of Ru+Ru and Zr+Zr at s N N = 200 GeV with the STAR detector at RHIC. The polarization dependence on collision centrality exhibits an increasing trend in more peripheral collisions. Λ and Λ ¯ polarization dependence on the transverse momentum and pseudorapidity have been investigated, but no significant dependence was observed. The polarizations of Λ and Λ ¯ are found to be consistent with each other, indicating little contribution of the spin-magnetic coupling to the measured polarization. Comparison to previously measured polarization in Au+Au collisions show no obvious system size dependence. The results are qualitatively consistent with hydrodynamic calculations including contributions from shear-induced polarization and thermal vorticity. For the first time in heavy-ion collisions, the dependence of the global polarization on the hyperon’s emission azimuthal angle relative to the second-order event plane has been measured, indicating stronger polarization for the in-plane emitted hyperons at the level of 2.4 σ significance in 20–50 % centrality. The Ξ hyperon polarization measurements via polarization transfer analysis yield finite positive values with 2.9 σ significance in 20–50 % centrality, slightly larger compared to the inclusive Λ polarization. © 2025 The Authors.
Keywords: Global polarization; Hyperon; Vorticity; dept.phy

Erratum: Disappearance of partonic collectivity in √ sNN = 3 GeV Au+Au collisions at RHIC (Physics Letters B, (2022), 827, 137003) - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN = 3 GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4 GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3 GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3 GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions. © 2025 The Authors.
Keywords: Baryonic interactions; Collectivity; High baryon density; NCQ scaling; STAR experiment; dept.phy